Tingkat Keterampilan Menggiring Bola Siswa Ekstrakurikuler Futsal - Hasyim Hasyim; Nurliani Nurliani; Hasbi Asyhari (Departement of Mathematics Education, 2023)
This research is a quantitative descriptive study that aims to determine the level of dribbling skills in Futsal Extracurricular Students at SMA Negeri 4 Makassar. The variable in this study is the single variable, namely the skills of dribbling the Futsal Extracurricular Students at SMA Negeri 4 Makassar. The population in this study were all students participating in Futsal extracurricular at SMA Negeri 4 Makassar, while the sample in this study were 15 students participating in futsal extracurricular at SMA Negeri 4 Makassar. From the results of data analysis, it can be concluded that the level of driving skills of Futsal Extracurricular Students at SMA Negeri 4 Makassar is categorized as